2019
DOI: 10.1002/jsfa.9809
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation delay of sunflower oil under frying by moringa oil addition: more than just a blend

Abstract: BACKGROUND: Blending Moringa oleifera oil (MOO) with other oils of recognized lower stability under prolonged frying results in oxidation delay. The present study aimed to detail the probable molecular interactions supporting these observations, using a small amount of MOO (20%) and sunflower oil (SFO; 80%) under domestic deep-frying conditions (intermittent frying of fresh potatoes, 180 ∘ C, 2 × 90 min day −1 , 5 days). RESULTS: Blending 20% MOO with SFO resulted in a significantly lower formation of polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The high antioxidant activity of sesame oil and its blend with corn oil demonstrating interaction of their antioxidants ( Table 2 ). The results showed that blended oils were more stable to oxidation which is in agreement with results of Boukandoul et al [ 32 ], Bhatnagar et al [ 26 ], and Abdel-Razek [ 33 ]. The blending of oils would increase the natural antioxidants, MUFA, and PUFA which could increase the ability of samples to scavenge DPPH [ 26 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The high antioxidant activity of sesame oil and its blend with corn oil demonstrating interaction of their antioxidants ( Table 2 ). The results showed that blended oils were more stable to oxidation which is in agreement with results of Boukandoul et al [ 32 ], Bhatnagar et al [ 26 ], and Abdel-Razek [ 33 ]. The blending of oils would increase the natural antioxidants, MUFA, and PUFA which could increase the ability of samples to scavenge DPPH [ 26 ].…”
Section: Resultssupporting
confidence: 91%
“…The p-AV of fresh oil samples varied from 5.69 to 10.05. The higher amount of aldehydes in fresh oils is attributed to the preservation of aldehydes during partial refining and cannot be considered as oxidation markers [ 32 ]. The results of p-AV of different oil samples were varied during three days of frying.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tocols are also used for the extension of shelf life and the stabilization of food. Tocopherols play an important role in preventing the oxidation of almond lipids, resulting in increasing the possibility of lengthening kernel storage [5][6][7]. Recently, the cosmetic industry and clinical dermatology have paid more attention to tocols due to their photoprotection and antioxidant properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…The varied fatty acid composition, monounsaturated and polyunsaturated, of the G. max and H. annus oils contribute aggregating more diversity to the C. nucifera oil profile. Therefore, the oil blends are more complete, have more variety and more balanced amount of fatty acids when compared to their pure oils (Boukandoul et al, 2019).…”
Section: Resultsmentioning
confidence: 99%